Microstructural modification, mechanical properties, and wear behaviour of aged Al–Si–Mg/Si3N4 composites for aerospace applications - Chinmay Mundayadan Chandroth; Jithin Vishnu; Bassiouny Saleh; K.R. Ananthakrishnan; Deva Narayan A; Aswin R. Kurup; Sidharth S; Karthik V. Shankar (International Journal of Lightweight Materials and Manufacture)
The main objective of the present research is to probe how ageing time influences the morphological, mechanical, and wear behaviour of stir cast Al–Si–Mg alloy, reinforced with 10 wt% Si3N4 particles subsequently heat treated in T6 condition. The findings reveal that the presence of Si3N4 reinforcements, followed by the heat treatment, enhances the mechanical and tribological properties of the composite. The ensuing mechanical properties show significant improvement prior to aging heat treatment (180 °C/4h), reaching a hardness of 120.8 HV (45 % increase) and tensile strength of 275 MPa (50 % increment), respectively compared to as-cast composite. Fractography reveals dimples, transgranular cleavage surfaces, cracks, and micro-ploughing. Among the samples tested, the composite aged for 4 h (180 °C/4h, ASN-4) demonstrates the lowest wear rate. Abrasive and adhesive wear in combination is the primary wear mechanism in these samples. Overall, this research provides insights for research endeavors in manufacturing various components in the aerospace industry.